PRINCIPLE OF LEGAL BENEFIT IN THE ELEMENT OF RETURN OF STATE LOSSES - Khomaini, Mhd. (Jurnal Hukum Khaira Ummah, 2024)
Legal philosophy explains the principle of utility in every Legal Policy. However, at the level of legal awareness in society, this principle is often neglected. Legal problems that are biased towards utility values conflict with legal certainty carried out by law enforcers. This article aims to analyze the principle of legal utility in efforts to return state losses in the construction of ATCS (Area Traffic Control System) in Tarakan City. The research method used is normative juridical with a conceptual approach, statutory regulations and case studies. The orientation of the analysis is based on the theory of legal philosophy, especially the principle of utility. The results of the study found that there was a phenomenon of attraction of interests of perpetrators of alleged corruption that was concrete, casuistic and particular.